Tolerance according to Imām Bukhārī - Ahmad Muhammad Abd Al Azhim Farhat (Pascasarjana Universitas Wahid hasyim Semarang, 2015)
It is undeniably that many people assumed the people of hadith (ahl al-hadis) practice Islam rigidly and understand al-Qur’an and hadith literally. This article tries to reveal the hadith scholar’s thoughts, Imam Abu Ismail al-Bukhari, on tolerance clearly. His biography was full of tolerance pearls and wisdom and of soul to prioritize and ease other people’s affairs. Additionally, he also paid a great attention to Muslim problems. This study used a descriptive analytical method in which the writer explores the sources and references related to him from his biography and persistence in narrating hadith and Islamic scholars’s opinion about him as well. To get focus more on this study, it is divided into two parts: First, Imam Bukhari’s tolerant attitude towards others such as commercial transaction, relationship with servant, slave, and pupils even with haters. Second, Imam Bukhari’s tolerance in narrating the hadith such as how he received and narrated hadith and how he compiled and titled the chapters in his kitab ash-sahih. All strongly emphasized that he has noble characters especially tolerance. Keywords: al-Bukhari; tolerance; hadith